Tumor-derived microvesicles induce, expand and up-regulate biological activities of human regulatory T cells (Treg). - Marta Szajnik; Malgorzata Czystowska; Miroslaw J Szczepanski; Magis Mandapathil; Theresa L Whiteside (PLoS ONE)
Background Tumor-derived microvesicles (TMV) or exosomes are present in body fluids of patients with cancer and might be involved in tumor progression. The frequency and suppressor functions of peripheral blood CD4(+)CD25(high)FOXP3(+) Treg are higher in patients with cancer than normal controls. The hypothesis is tested that TMV contribute to induction/expansion/and activation of human Treg. Methodology/principal findings TMV isolated from supernatants of tumor cells but not normal cells induced the generation and enhanced expansion of human Treg. TMV also mediated conversion of CD4(+)CD25(neg) T cells into CD4(+)CD25(high)FOXP3(+) Treg. Upon co-incubation with TMV, Treg showed an increased FasL, IL-10, TGF-beta1, CTLA-4, granzyme B and perforin expression (p<0.05) and mediated stronger suppression of responder cell (RC) proliferation (p<0.01). Purified Treg were resistant to TMV-mediated apoptosis relative to other T cells. TMV also increased phospho-SMAD2/3 and phospho-STAT3 expression in Treg. Neutralizing Abs specific for TGF-beta1 and/or IL-10 significantly inhibited TMV ability to expand Treg. Conclusions/significance This study suggests that TMV have immunoregulatory properties. They induce Treg, promote Treg expansion, up-regulate Treg suppressor function and enhance Treg resistance to apoptosis. Interactions of TMV with Treg represent a newly-defined mechanism that might be involved in regulating peripheral tolerance by tumors and in supporting immune evasion of human cancers.